The Interests of Democracy or the Eradication of Corruption: The Dissolution of Political Parties in a Review of Law and Practice in Other Countries - Mutawalli Mukhlis , Muhammad; Bin Paidi, Zulhilmi; Wiranti, Wiranti (Constitutional Law Review, 2025)
Dissolution of political parties as a legal response to systemic corruption raises fundamental questions about the balance between democratic integrity and political accountability. In the Indonesian context, political parties function as pillars of representative democracy, yet have increasingly been implicated in corruption scandals that benefit the party institutionally. The current legal framework—anchored in Article 24C of the 1945 Constitution and Law No. 2 of 2008—limits dissolution to violations of ideological and constitutional principles, excluding corruption from explicit consideration. This normative gap weakens the state’s capacity to enforce accountability. Through a normative-juridical and comparative approach, this study analyzes the theoretical justifications and practical mechanisms for dissolving political parties involved in systemic corruption. Case studies from Germany, Turkey, and South Korea demonstrate how other constitutional democracies integrate financial misconduct into their criteria for party dissolution. The findings support the need to reinterpret constitutional threats to include entrenched corruption as an assault on democratic order. Drawing on the theories of militant democracy, corporate criminal liability, and organizational accountability, this article advocates for legal reform that enables the Constitutional Court to act decisively against parties that exploit democratic institutions for corrupt purposes, while still preserving procedural fairness and political pluralism.